Paraconsistent annotated logic in viability analysis: an approach to product launching - Carvalho, F. R. de (2004)
In this paper we present an application of the Para-analyzer, a logical analyzer based on the Paraconsistent Annotated Logic Ptau, introduced by Da Silva Filho and Abe in the decision-making systems. An example is analyzed in detail showing how uncertainty, inconsistency and paracompleteness can be elegantly handled with this logical system. As application for the Para-analyzer in decision-making, we developed the BAM - Baricenter Analysis Method. In order to make the presentation easier, we present the BAM applied in the viability analysis of product launching. Some of the techniques of Paraconsistent Annotated Logic have been applied in Artificial Intelligence, Robotics, Information Technolgy (Computer Sciences), etc. [2].